Permanence of Chapter IV of the Preliminary Title of the Spanish Civil Code : The conflict rule and its problems of implementation - Calvo Caravaca , Alfonso-Luis; Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This work is a balanced analysis of the importance of the reform of the Preliminary Title of the Civil Code with regard to the ancillary rules contained in art. 12 of that Code. All solutions offered by the aforementioned legal rule and their application by Spanish courts during the last fifty years are addressed. Likewise, the progress that those solutions meant for Spanish private international law is also analyzed and what remains of them in a world, that of the 21st century, which bears very little resemblance to the world of 1974.
Keywords: Private international law; Preliminary Title of the Civil Code; application rules; public policy; renvoi; charasterisation; States with more than one legal system; evasion of the law; general rules of private international law.